The Effect of Audit Risk, Business Complexity, and Team Discussion on Audit Supervision - Ricky Bryan D.P. Tampubolon (CV. ITTC INDONESIA, 2026)
This study examines the influence of audit risk, business complexity, and team discussion on audit supervision. The research is motivated by the increasing importance of effective audit supervision in maintaining audit quality, especially when auditors face high levels of risk and complex client environments. The objective of the study is to empirically test whether audit risk, business complexity, and team discussion significantly affect the effectiveness of audit supervision. This study employs a quantitative explanatory survey design, with external auditors working in Public Accounting Firms (KAP) in Jakarta as the research subjects. A total of 144 respondents were selected through purposive sampling. Data were collected using structured questionnaires measured on a five-point Likert scale, and analyzed using multiple linear regression with SPSS. The results reveal that audit risk has a positive and significant effect on audit supervision, indicating that higher audit risk requires more intensive supervision. Business complexity shows a negative and significant effect on audit supervision, suggesting that more complex client structures and operations pose greater challenges to supervisory effectiveness. Meanwhile, team discussion has a positive and significant effect, demonstrating that communication and collaboration among team members strengthen supervisory practices. The study concludes that managing audit risk, understanding client complexity, and optimizing team discussions are crucial in enhancing audit supervision. It is recommended that auditors allocate more resources when facing high audit risk, adopt adaptive supervisory approaches for complex clients, and encourage structured and inclusive team discussions to ensure consistent and high-quality audit outcomes.